STEADY GROUNDWATER FLOW THROUGH MANY CYLINDRICAL INHOMOGENEITIES IN A MULTI-AQUIFER SYSTEM - Bakker M. (My University, 2003)
A new approach is presented for the simulation of steady-state groundwater flow in multi-aquifer systems that contain many cylindrical inhomogeneities. The hydraulic conductivity of all aquifers and the resistance of all leaky layers may be different inside each cylinder. The approach is based on separation of variables and combines principles of the theory for multi-aquifer flow with principles of the analytic element method. The solution fulfills the governing differential equations exactly everywhere; the head, flow, and leakage between aquifers may be computed analytically at any point in the aquifer system. The boundary conditions along the circumference of the cylinder are satisfied approximately, but may be met at any precision. Two examples are discussed to illustrate the accuracy of the approach and the significance of inhomogeneities in multi-aquifer systems. The first application simulates the vertical and horizontal, advective spreading of a conservative tracer in a homogeneous aquifer that is overlain by an aquifer with cylindrical inclusions of higher permeability. The second application concerns the three-dimensional shape of the capture zone of a well that is screened in the bottom aquifer of a three-aquifer system. The capture zone extends to the top aquifer due to cylindrical holes of lower resistance in the separating clay layers.
Keywords: MULTI-AQUIFER; INHOMOGENEITIES; ANALYTIC ELEMENT METHOD; CAPTURE ZONE